Аналіз схем розгортання ключів блокових симетричних шифрів - Горбенко, І. Д.; Шапочка, Н. В. (ХНУРЭ, 2008)
Key expansion scheme is carried out in this work. Cryptographic analysis methods concerned to key expansion scheme are considered. Projects of block symmetric ciphers are presented and requirements to key expansion schemes are studied. Because of serious deficiency the national algorithm "Kalina" is studied and requirements to its key expansion scheme are proposed.
Keywords: блоковий симетричний шифр; розгортання ключів шифрів